2009
DOI: 10.1074/jbc.m806716200
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme K Displays Highly Restricted Substrate Specificity That Only Partially Overlaps with Granzyme A

Abstract: Granzymes are serine proteases stored in cytolytic granules of cytotoxic lymphocytes that eliminate virus-infected and tumor cells. Little is known about the molecular mechanism and function of granzyme (Gr)K. GrK is similar to GrA in that they are the only granzymes that display tryptase-like activity. Both granzymes induce cell death by single-stranded nicking of the chromosomal DNA by cleaving the same components of the endoplasmic reticulum-associated SET complex. Therefore, GrK may provide a backup and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 33 publications
(76 reference statements)
1
93
1
Order By: Relevance
“…As expected, only Tc cells from LCMV-immune B6 but not from gzmAxB À/À and perfxgzmAxB À/À mice expressed gzmA and gzmB proteins (data not shown). (Mo)gzmK manifested enzymatic activity and to verify their predicted differences in cleavage specificity, 12 their amidolytic activities were compared against four different chromogenic substrates. Both gzms were proteolytically active, with each exhibiting distinct preferences for the four related chromogenic substrates, especially Tos-Gly-pro-ArgpNA (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, only Tc cells from LCMV-immune B6 but not from gzmAxB À/À and perfxgzmAxB À/À mice expressed gzmA and gzmB proteins (data not shown). (Mo)gzmK manifested enzymatic activity and to verify their predicted differences in cleavage specificity, 12 their amidolytic activities were compared against four different chromogenic substrates. Both gzms were proteolytically active, with each exhibiting distinct preferences for the four related chromogenic substrates, especially Tos-Gly-pro-ArgpNA (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…12 Similar to (Hu)gzmA, the original report indicated that isolated Rat and (Hu)gzmKs are cytotoxic in vitro. 13 A more recent study has suggested that isolated (Hu)gzmK induces biochemical events similar to (Hu)gzmA in target cells.…”
mentioning
confidence: 99%
“…21,34 Interestingly, many members of the hnRNP protein family have also been identified as potential substrates of other granzymes than GrM. [35][36][37][38] Further studies It remains an intriguing question why GrM targets viral pp71 17 and host cell hnRNP K to attack the initial IE events of HCMV replication rather than just killing HCMV-infected cells. Consistent with our findings, IE1-and pp65-specific CD4 þ T cells and CD8 þ T cells can recognize and kill IE1 and pp65 peptide-loaded target cells, but fail to induce cell death in HCMV-infected target cells after recognition and degranulation, whereas HCMV replication is efficiently inhibited 39,40 (Dr. MR Wills, personal communication (Department of Medicine, University of Cambridge, Cambridge, UK)).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above mentioning and results of this study, GZMK may play a crucial role in facilitating the degradation of tubulobular structures and translocation of spermatids. Th e tubulobular structures in testes are made by microtubules , and GZMK, a tryptase, specifi cally targets of β-tubulin (Bovenschen et al 2009). Moreover, microtubules are abundant in the Sertoli cell cytoplasm, are oriented in the direction of the spermatid translocation and surround the cisterns where spermatids remain embedded (Redenbach et al 1992;Vogl et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, GZMK may also initiate germ cell apoptosis and have a role in the degradation of the apoptotic bodies in testes. GZMK induce apoptosis independently of the caspase-mediated pathways through the nuclear morphological changes and single-strand DNA breaks (Bovenschen et al 2009). Even though, GZMK staining was absent in the nuclei of the same germ cell stages in the seminiferous tubule that showed apoptosis aft er EDS treatment.…”
Section: Discussionmentioning
confidence: 99%